The Tradition of Bancaan on Friday Night Wage A Study of Living Hadith in the Village of Cangkring B Karanganyar Demak - Luthfiyani, Melisa; Friyadi, Arif (el Buhuth: Borneo Journal of Islamic Studies, 2025)
The Friday Wage bancaan tradition is a tradition that is alive and believed by the community until now, the tradition is passed down from generation to generation. This tradition is used to show gratitude and thanks to God for giving health and safety. The purpose of this research article is to describe the history, process, values and benefits of Friday Wage bancaan. This research uses a qualitative descriptive approach and uses two types of data, namely primary and secondary. The primary data comes from interviews while the secondary data comes from literature or review studies of journals, books and other literature that has a relationship with related discussions. The results of this study indicate that the bancaan tradition has many social values and benefits for the community. This research also presents hadiths that are relevant to the hadiths that animate the community (living). This research article is expected to add insight and knowledge to the community, especially to the younger generation to always maintain and preserve their culture.